Visualização de dados no cenário da data science: práticas de laboratórios de inovação guiados por dados - Rodrigues, Adriana Alves (2019)
It investigates the impact of data visualization and Big Data and its unfolding in the context of Data Science and Information Science. The thesis defends the existence of disruptive narratives of data-guided visualization in innovation laboratories and is an emerging reconfiguration process for new formats as it was in its origin with the "information explosion" in the 1940s. As a methodology, the research is qualitative and quantitative, constituting a case study based on the empirical object of the Laboratory of Image and Cyberculture Studies (LABIC). In addition, we used an ethnographic approach based on non-participant observation and semi-structured interviews of laboratory practices of data-guided innovation aiming at the structuring of Data Visualization, monitoring of these productions, adding to the bibliographic research that permeates an interdisciplinary theoretical reference on Science Information Technology, Information Design, Big Data, Data Science and Data Visualization, Theory of Disruptive Innovation. As a result, research has identified in the case study that innovative practices can construct disruptive narratives of Data-Driven Visualization from the exploitation of large data volumes (Big Data) in the context of Data Science.